Digital marketing in mountain tourism: Challenges of the new time and development priorities - Purhani Safar Hasan; Mamedova Sevda Binyat; Mukumova Dilrabo; Esanmurodova Nilufar (BIO Web of Conferences)
The tourism industry is increasingly playing a special role in the economy of countries, regions, cities and individual locations. It not only becomes a source of replenishment of territorial budgets directly, but also contributes to the development of small and medium-sized businesses, contributes to the creation of new jobs, influences the technological and digital transformation of territories. Modern conditions impose their own restrictions on the development of the industry and, at the same time, open up new opportunities for domestic tourism in Russia. The purpose of the study was to identify structural changes and trends in the development of the tourism industry in connection with demographic, socio-economic, epidemiological and foreign policy transformations. The author of the article updated the role of territorial marketing and presented proposals for its transformation taking into account the challenges of the new time. The main research methods are content analysis, evaluation of statistical information, spatio-temporal analysis. Based on an in-depth study of trends, new marketing tasks for territorial authorities and tourism market participants in the creation and promotion of destinations are substantiated. The territorial marketing tools proposed by the author, aimed at attracting tourists and developing the tourism industry as part of the territorial economy as a whole, take into account modern trends in the development of commercial marketing and are adapted to the conditions and capabilities of individual destinations. The issues of transformation of territorial labor and service markets in the context of the development of the tourism industry are covered. The key conclusion is the need to revise the conceptual approaches of locations to the issues of building territorial marketing and implementing marketing strategies. The author proposes measures, the implementation of which will make the socio-economic development of territories more sustainable and effective in a rapidly changing world.